Beating, ditching and hiding: consumers’ everyday resistance to marketing - Heath, Teresa; Cluley, Robert; O’Malley, Lisa (Taylor and Francis, 2017)
This article illuminates consumers’ views of marketing in light of theories of resistance. It argues that consumers engage in resistance to the power of marketing through their everyday actions and also through the ways they construct their accounts of these actions. It identifies three theoretical approaches to resistance (hegemonic, relational and autonomous). These are used to discuss consumers’ accounts of marketing collected through 78 personal interviews in which participants were asked to describe marketing and provide examples of their experiences with marketing as they defined it. Through this, the study uncovers various forms of consumer resistance, which can often go unnoticed. These are conceptualised through the notion of everyday resistance to marketing and are used to challenge existing marketing theory and develop paths for future research.